Knowledge translation in global urban agendas: A history of research-practice encounters in the Habitat conferences. (October 2019) - Cociña, Camila; Frediani, Alexandre Apsan; Acuto, Michele; Levy, Caren
Highlights: Approaches to 'urban equality' and 'knowledge translation' have changed in the history of the Habitat conferences. The pathways that have led to the current 'global urban agenda' are as telling as the agendas themselves. Paradigms about knowledge have moved from building collective narratives, to targeting performance, to measurable data. The approaches to urban equality have changed influenced by international development processes and power relationships. Cases of community-based actors help to interrogate politics of knowledge circulation between global-local urban agendas. Abstract: The relationship between planning research and practice plays a key role in shaping global commitments related to urban development. Arguably, this is the case for a 'global urban agenda' being articulated at an international scale via frameworks like the Sustainable Development Goals and the New Urban Agenda. These multilateral commitments have been shaped by power relationships and assumptions about what kind of knowledge is valuable at different historical moments, a recognition of the local and global impacts of urban development and what sort of urban development is desirable at specific historical junctures. The pathways that have led to the present global attention to cities are as telling as the frameworks themselves. In this paper, we explore the history of multilateral and international networks that have shaped today's global urban agenda. We focus on the three United Nations Conference on Housing and Sustainable Urban Development (Habitat I, II and III) as milestones in the evolution of this agenda. Drawing on Southern urban theory and current debates on the interaction of practitioners and academics, we discuss the paradigms that have shaped the ways in which knowledge has been articulated, circulated and valued in those historical moments via the concept of 'knowledge translation'. We discuss the way in which 'urban equality' has been approached and explored in the praxis of these agendas. To do so, the paper discusses community-based cases that can highlight the different knowledge paradigms, and the power dynamics behind them, opening up questions about the challenges of including diverse voices and knowledges in the 'global' conversation on urban agendas.